Penerapan Konsep NoSQL Pada Perangkat Lunak Manajemen Properti: Penerapan Konsep Nosql Pada Perangkat Lunak Manajemen Properti - Jumaida; Alek Wijaya (STMIK Budi Darma, 2023)
Currently, technology is widely used to assist in business operations. Various fields have utilized it, such as the property sector. Typically, developers managing databases use SQL databases, which involve related queries. However, with technological advancements, developers are interested in using NoSQL databases to manage data in order to cope with the increasing volume of data. NoSQL database management is well-suited for handling large databases and offers various data models, including graph-based, document-oriented, column-oriented, and key-value. The results of this research indicate that implementing NoSQL concepts in property management software can improve the efficiency and performance of property data management. The use of NoSQL databases allows for flexible schemas, horizontal scalability, high performance, and global scalability. Consequently, this software can provide users with convenience, enabling them to enhance operational efficiency in property management